2010
DOI: 10.1063/1.3463720
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-assisted single base-pair mismatch discrimination on a microfluidic microarray device

Abstract: Two simple gold nanoparticle ͑GNP͒-based DNA analysis methods using a microfluidic device are presented. In the first method, probe DNA molecules are immobilized on the surface of a self-assembled submonolayer of GNPs. The hybridization efficiency of the target oligonulceotides was improved due to nanoscale spacing between probe molecules. In the second method, target DNA molecules, oligonulceotides or polymerase chain reaction ͑PCR͒ amplicons, are first bound to GNPs and then hybridized to the immobilized pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…colorimetric, fluorescence) can result from the close proximity between AuNPs released upon DNA hybridization with complementary ssDNA. [15][16][17][18][19][20][21] Previous work by Li et al demonstrated the use of binding of DNA to AuNPs for applications in which the AuNPs were used to hold onto the ssDNA as a cargo in assisting single base pair discrimination, 24,25 but the mechanism of this discrimination is yet to be determined (vide infra).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…colorimetric, fluorescence) can result from the close proximity between AuNPs released upon DNA hybridization with complementary ssDNA. [15][16][17][18][19][20][21] Previous work by Li et al demonstrated the use of binding of DNA to AuNPs for applications in which the AuNPs were used to hold onto the ssDNA as a cargo in assisting single base pair discrimination, 24,25 but the mechanism of this discrimination is yet to be determined (vide infra).…”
mentioning
confidence: 99%
“…[10][11][12][13] Through further research, Li et al have determined that AuNP-loaded DNA targets (AuNPtargets), in contrast to the DNA targets freely dissolved in the buffer solution (free-targets), were able to discriminate between the PM immobilized probe from the single base-pair mismatched (MM) probes when unaided by thermal stringency at room temperature. 24,25 We hypothesized that AuNPs compete with the immobilized probes to gain the target binding, which increases the stringency of the hybridization process. During this competitive process the MM duplex formation with a lower hybridization affinity would be influenced more strongly by the presence of AuNPs than the formation of PM duplex.…”
mentioning
confidence: 99%
“…In our group, we have previously employed the MMA chip for detection of DNA [37][38][39] and RNA targets. 40 The microfluidic microarray chip offers several advantages to other designs (e.g.…”
Section: R a F Tmentioning
confidence: 99%
“…Some of the common polymer materials used include polycarbonates (PCs) 14,15 and polydimethylsiloxane. 12,16,17 For this research, a polycarbonate compact disc base material was selected. Studies have shown that polycarbonate is PCR friendly.…”
Section: B Pcr Sample Chamber Design and Fabricationmentioning
confidence: 99%